Lead Exposure and Accumulation in Healthy Thais: Assessed by Lead Levels, EDTA Mobilization and Heme Synthesis-related Parameters - Winai Wananukul (2018)
Lead is one of the pollutants which is of public concern. The magnitude of lead contamination in Thai people is of interest. The objective of this study was to evaluate the lead status in normal healthy volunteers. Normal volunteers were included. The blood for lead level, Zinc protoporphyrin (ZPP), δ-aminolevulinic acid dehydratase (ALA-D) activity, and baseline urine for lead, δ-aminolevulinic acid (ALA) and coproporphyrinogen III (CP3) were collected. The EDTA mobilization test was done. 24 hour urine after administration of the drug was collected for lead analysis. Thirty volunteers were included in the study. All were men whose average age was 32.5±6.9 years. The mean lead level was 5.95±2.01 μg/dL and 5.83±2.32 μg/L in urine. The 24 hour urine lead contents before and after EDTA administration were significantly different (11.11±6.72 and 16.05±9.51 μg respectively). Blood ALA-D activity was 251.6±80.4 unit/ml of RBC. Urine ALA and CP3 were 0.56±1.2 mg/L and 22.17±23.9 μg/L respectively. All were in the normal ranges. All parameters suggested that the healthy Thai volunteers had an acceptable magnitude of lead exposure and accumulation.